'Hangry’ Drosophila: food deprivation increases male aggression - data - Edmunds, D; Edmunds, D; Perry, J (University of Oxford, 2020)
I created the data from spot-check behavioural observations of the experimental organism. The code was used to analyse the data and runs in the software programme, R